Free float and liquidity screening of the JSE - H. Andersen; F. Durand (South African Journal of Business Management, 2001)
Current index construction techniques screen potential index constituents in order to exclude those with a low liquidity and/or free float, the actual percentage of shares available for trade, to provide an improved performance benchmark.Four techniques have been applied to the JSE to determine an optimum benchmark. Three indices were constructed using the Financial Times Securities Exchange, Dow Jones STOXX and Morgan Stanley Capital International screening rules. The fourth was constructed by developing new rules. The study found that investors experienced free float and liquidity constraints and that a JSE free float index is required. It also showed that the American and British rules did not provide an improved index and that new, more appropriate rules were needed to create an optimum free float index.
Keywords: 650